The Influence of Organizational Communication on Teacher Job Satisfaction in SMPN 1 Banuhampu Agam District: Pengaruh Komunikasi Organisasi Terhadap Kepuasan Kerja Guru Pada SMPN 1 Banuhampu Kabupaten Agam - Nikmatul Husna (Perkumpulan Doktor Indonesia Maju, 2020)
The purpose of this research is to identify and analyze the influence of organizational communication toward work satisfaction in SMPN 1 Banuhampu Kabupaten Agam. The population of the research is the teachers in SMPN 1 Banuhampu Kabupaten Agam. Samples taken are 56 respondents by using random sampling technique, which determine samples by taking a sample randomly and use the questionnaire as a tool to collect data. Based on hypothesis in this research, it is assumed that the influence of organizational communication, significantly and positively influence the teachers’ work satisfaction in SMPN 1 Banuhampu Kabupaten Agam. The data analysis methods author used in this research are validity tes, reliability test, variable descriptive analysis test, simple linear regression analysis, T test and F test. From analysis that have been done, author found that effect of organizational communication variable (X) toward work satisfaction is significantly and positively influence the teachers’ work, this is proven by significant probability value of communication organization is resulted in 0,000 which is smaller than 0,05. From F test, it can be concluded that regression model can be use to predict the organizational communication, which have significantly and positively influence toward teachers’ work satisfaction by the significant probability value is resulted in 0,000 which is smaller than 0,05.